CHARACTERIZATION OF RESISTIVE NONLINEAR CIRCUIT ELEMENTS OF RADIO AND TELECOMMUNICATION SYSTEMS ON THE BASIS OF THE CONTROLLED DYNAMIC SATURATION CONCEPT - Gulin, S. P.; Gulin, A. S. (Radio Electronics, Computer Science, Control, 2010)
Algorithms of resistive nonlinear circuit elements (NSE) characterization are proposed based on the concept of controlled dynamic saturation. Incremental ratios «input – output» of NSE are hypergeometric Gauss series achieved using the dynamic saturation function (DSF). These ratios permit to unify the algorithm of convergent nonlinear inertial system (NIS) mathematical model formation in terms of Volterra – Gauss functional series and to calculate spectral characteristics of its response to multifrequency influence.